THE EFFECT OF ONLINE SERVICE QUALITY ON BERRYBENKA E-COMMERCE CUSTOMER SATISFACTION - Sabila, Elliza; Nurainun, Nurainun (RADJA PUBLIKA, 2022)
This study aims to see the effect of online service quality which consists of dimensions (ease of use, web design, responsiveness, customization and assurance) on customer satisfaction in Berrybenka e-commerce. This study used primary data obtained by distributing questionnaires to 110 respondents who were selected using a purposive sampling method. The data analysis method used is multiple linear regression method with the help of SPSS version 20. This study shows that ease of use has a significant effect on Berrybenka e-commerce customer satisfaction, web design has a significant effect on Berrybenka e-commerce customer satisfaction, responsiveness has a significant effect on customer satisfaction. Berrybenka ecommerce customer, customization has a significant effect on Berrybenka e-commerce customer satisfaction and assurance has a significant effect on Berrybenka e-commerce customer satisfaction. Simultaneously, ease of use, web design, responsiveness, customization and assurance have a significant effect on Berrybenka's e-commerce customer satisfaction